1993
DOI: 10.1177/0310057x9302100207
|View full text |Cite
|
Sign up to set email alerts
|

Background Infusion with Patient-Controlled Analgesia: Effect on Postoperative Oxyhaemoglobin Saturation and Pain Control

Abstract: The aim of this study was to determine whether the addition of a background infusion (BI) to patient-controlled analgesia (PCA) would lead to significantly improved pain control or poorer oxyhaemoglobin saturation (SpO2) after gynaecological surgery. Sixty-two patients were studied for 24 hours postoperatively; pain scores and morphine dose were recorded hourly, SpO2 was recorded every 10 seconds. Administration of the BI resulted in a significant increase in total morphine dose received although there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…2) and morphine-related frequency of side effects. The findings are partially consistent with previous clinical experiments in which the background infusion increased postoperative opioid usage [4][5][6][7], but with a similar pain intensity and an increased frequency of adverse effects [20]. An audit of large numbers of patients has shown the increased risks of respiratory depression [21,22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…2) and morphine-related frequency of side effects. The findings are partially consistent with previous clinical experiments in which the background infusion increased postoperative opioid usage [4][5][6][7], but with a similar pain intensity and an increased frequency of adverse effects [20]. An audit of large numbers of patients has shown the increased risks of respiratory depression [21,22].…”
Section: Discussionsupporting
confidence: 88%
“…Some studies comparing the two types of patient-controlled analgesia (PCA) suggest that users of continuous PCA infusion of morphine have similar postoperative pain intensity but consume more morphine and have a greater incidence of adverse effects [4][5][6][7][8]. However, one study reported better postoperative analgesia [9].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, it does not improve postoperative pain or sleep disturbance and simultaneously increases the incidence of opioid-related side effects. [8][9][10] A previous meta-analysis of 796 postsurgical patients reported that a basal opioid infusion of IV-PCA was significantly associated with a higher incidence of respiratory depression. 11 Therefore, routine use of basal opioid infusion in IV-PCA is no longer recommended in practice.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Most of the evidence regarding this issue has been deduced from morphine-based IV-PCA in studies that included a relatively small number of patients. [8][9][10] Due to the different pharmacokinetic properties of fentanyl, evidence of the risks and benefits of basal infusion in fentanyl-based IV-PCA is required. We hypothesized that fentanyl-based IV-PCA without basal infusion could reduce not only opioid-related side effects, but also opioid consumption, without increasing the postoperative pain intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation